(untitled) (Tidsskrift for Praktisk Teologi, 2020)
The article discusses pastoral theology as an academic discipline. In a first stage, I argue that it should be considered a sub-disicipline within practical theology, and be practiced as a hospitable meeting place for cross-disciplinary research on clergy and religous leaders. Secondly, I discuss the relationship of pastoral theology, with its long tradition dating back to premodern days, to empirical and contextual theologies. I argue that the latter are important renewers and critics, whereas at the same time, pastoral theology should not give up on its particular characteristic of introducing students to pastoral practices. In a final section, I point to a way forward for the discipline, suggesting that it should relate three recent controversial topics (religious power, inter-religious dialogue, and new forms of ministry) and three classical pastoral theological terms (the pastor, the professional and the spiritual).